2014
DOI: 10.3892/etm.2014.1719
|View full text |Cite
|
Sign up to set email alerts
|

Green tea catechin, epigallocatechin-3-gallate, attenuates the cell viability of human non-small-cell lung cancer A549 cells via reducing Bcl-xL expression

Abstract: Clinical and epidemiological studies have indicated that the consumption of green tea has a number of beneficial effects on health. Epigallocatechin-3-gallate (EGCg), the major polyphenolic compound present in green tea, has received much attention as an active ingredient. Among the numerous promising profiles of EGCg, the present study focused on the anticancer effects. Apoptosis induced by EGCg and subsequent cell growth suppression have been demonstrated in a number of cell culture studies. However, the und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 33 publications
1
27
0
Order By: Relevance
“…The mechanism of apoptotic cell death is believed to be through down-regulation and/or suppression of cell deathinhibiting gene Bcl-xL (Sonoda et al 2014). A down-regulation of ku70 by interrupting its binding with Bax mRNA and drug-metabolizing enzymes such as cytochrome P450 and peroxidoredoxin-V has been suggested as possible mechanism of action for cancer treatment Maliakal et al 2011;Ren et al 2011).…”
Section: Mechanism Of Action Of Egcgmentioning
confidence: 99%
“…The mechanism of apoptotic cell death is believed to be through down-regulation and/or suppression of cell deathinhibiting gene Bcl-xL (Sonoda et al 2014). A down-regulation of ku70 by interrupting its binding with Bax mRNA and drug-metabolizing enzymes such as cytochrome P450 and peroxidoredoxin-V has been suggested as possible mechanism of action for cancer treatment Maliakal et al 2011;Ren et al 2011).…”
Section: Mechanism Of Action Of Egcgmentioning
confidence: 99%
“…Most previous studies evaluated the capability of teas inhibiting the proliferation of cancer cells or tumor growth utilizing either ethanol extracts or the main bioactive ingredient of teas as agents, such as catechins and EGCG (Chen et al., 2015; Shi et al., ; Sonoda et al. ; Tsai and Chen ). Tea remains one of the most popular beverages in the world, and the most common method of tea infusion preparation is by placing tea leaves or leaf powder into boiling water.…”
Section: Discussionmentioning
confidence: 99%
“…The other polyphenolic compound epigallocatechin‐3‐gallate (EGCG) that is mostly found in green tea ( Camellia sinensis ) leaves, has been shown to be beneficial for human health and to have antioxidant and anticancer activities (Kim, Quon, & Kim, ). It has shown that mRNA expression of antiapoptotic Bcl‐xL in A549 lung cancer cells was significantly downregulated after treatment with EGCG in vitro (Sonoda et al, ). Considering NF‐κB signaling governs Bcl‐xL transcription, EGCG suppresses Bcl‐xL mRNA and protein expression through the regulation of NF‐κB signaling (Sonoda et al, ).…”
Section: Natural Product‐derived Compounds As Potent Inducers Of Cellmentioning
confidence: 99%
“…It has shown that mRNA expression of antiapoptotic Bcl‐xL in A549 lung cancer cells was significantly downregulated after treatment with EGCG in vitro (Sonoda et al, ). Considering NF‐κB signaling governs Bcl‐xL transcription, EGCG suppresses Bcl‐xL mRNA and protein expression through the regulation of NF‐κB signaling (Sonoda et al, ).…”
Section: Natural Product‐derived Compounds As Potent Inducers Of Cellmentioning
confidence: 99%